2011
DOI: 10.1158/1055-9965.epi-10-0684
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Prostate Cancer Aggressiveness among African and Caucasian Americans in a Population-Based Study

Abstract: Background: This study evaluated obesity and prostate cancer aggressiveness relationship in a populationbased incident prostate cancer study.Methods: The North Carolina-Louisiana Prostate Cancer Project includes medical records data for classification of prostate cancer aggressiveness at diagnosis by using clinical criteria for 1,049 African American (AA) and 1,083 Caucasian American (CA) participants. An association between prostate cancer aggressiveness and obesity, measured using body mass indices (BMI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 38 publications
(42 reference statements)
7
34
0
Order By: Relevance
“…In our study, similarly to recent literature, we found that obesity was significantly associated with increased high-grade PCa [1]- [3]. Particularly, men had a greater than 2-fold increased risk of high-grade disease, compared with non-obese men.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, similarly to recent literature, we found that obesity was significantly associated with increased high-grade PCa [1]- [3]. Particularly, men had a greater than 2-fold increased risk of high-grade disease, compared with non-obese men.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the North Carolina-Louisiana Prostate Cancer Project, which included 1,049 African-American men and 1,083 Caucasian-American males, found that (overall) men with a WHR > 0.98 (compared with those with a WHR < 0.90) had an increased risk of highly aggressive disease (OR, 1.42; 95% CI, 1.00-2.00; ref. 13). However, when the data were stratified by race, the results showed that larger WHR (taken at the time of interview) was not related to prostate cancer risk in men of African origin (OR, 1.18; 95% CI, 0.76-1.83) but was significantly associated with aggressive cancer in men of European descent (OR, 2.03; 95% CI, 1.10-3.74).…”
Section: Waist To Hip Ratiomentioning
confidence: 86%
“…The findings from these studies have been inconsistent, with higher waist circumference implicated as increasing total prostate cancer risk in one study of African-American men in Michigan (12) but not another including men from Jamaica (11). The Jamaican study, however, reported that larger WHRs increased risk among high grade and all prostate cancer cases, whereas race-stratified data from a study in North Carolina did not corroborate these findings (13). The role of abdominal obesity on prostate cancer risk thus remains unclear, particularly among men of African descent.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Differences in blood glucose level (i.e., high glucose (≥5.6 mM) vs. diabetes (≥11.1 mM)) may have exaggerated these differences, as only 22 of 204 prostate cancer cases had physician diagnosed diabetes in our study. Given the central role of obesity in MetS and its high prevalence in the US population, it is also possible that duration of obesity (or elevated blood glucose) may be an important factor in prostate cancer development through oxidative stress induced cell proliferation, reduced adiponectin levels, and hyperinsulinemia induced prostate/ colon cancer cell proliferation [3,4,32,33]. When taken together, the discrepancy between the findings may be due to variation in: i) confounding variables and sample (i.e.…”
Section: Mets Components and Site-specific Cancermentioning
confidence: 99%